Volume 1: Turbomachinery 1994
DOI: 10.1115/94-gt-246
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Rotor/Rotor Interaction in a Hydrodynamic Torque Converter Using Hot-Film Anemometry

Abstract: Unsteady flow measurements were performed to investigate the internal flow field of a torque converter, especially unsteady rotor/rotor-interaction in the region between pump exit and turbine inlet. Superscripts simple ensemble average double ensemble average

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Kraus, Flack, Habsieger, Gillies, and Dullenkopf (2005) studied the unsteady flow induced by the pump/turbine blades passing. It was observed that the turbine inlet flow is significantly periodic and the pump exit flow shows independence of the turbine blades passing, similar to the results obtained by Browarzik (1994). Brun and Flack (1997) measured the unsteady velocity field in the turbine through laser velocimetry at two typical speed ratios: 0.065 and 0.800.…”
Section: Introductionsupporting
confidence: 78%
“…Kraus, Flack, Habsieger, Gillies, and Dullenkopf (2005) studied the unsteady flow induced by the pump/turbine blades passing. It was observed that the turbine inlet flow is significantly periodic and the pump exit flow shows independence of the turbine blades passing, similar to the results obtained by Browarzik (1994). Brun and Flack (1997) measured the unsteady velocity field in the turbine through laser velocimetry at two typical speed ratios: 0.065 and 0.800.…”
Section: Introductionsupporting
confidence: 78%
“…6 as curve (3). Compared with the experimental data, it results in values that are too small by about 17%.…”
Section: (7) For Reynolds Numbersmentioning
confidence: 97%
“…Unsteady flow between the pump and turbine impellers was measured by hot-film anemometry by Browarzik (3) in a detailed study of the effect of the pump-turbine interaction on flow fields. Gruver, Flack and Brun (4) - (7) used a laser Doppler velocimeter to investigate the internal flow in the pump and turbine impellers.…”
Section: Introductionmentioning
confidence: 99%
“…Others have performed studies of the flow fields in torque converters, including Browarzik (1994), Ejiri and Kubo (1998), Marathe and Lakshminarayana (1997), and Watanabe and colleagues (1997). Efforts at the University of Virginia have used nonintrusive laser velocimetry to map out the detailed flow fields discussed by, for example, Brun and Flack (1994) and Whitehead (1995).…”
mentioning
confidence: 97%